ANALISIS PELAYANAN KEBIDANAN DENGAN KEPUASAN IBU HAMIL DALAM ANTENATAL CARE - Dewi Sartika; Jitasari Tarigan Sibero; Nurrahmaton - (Jurnal Maternitas Kebidanan, 2023)
Introduction : Quality health services should performe by competent health personnel, firmly hold the philosophy, guided by ethics and the code of conduct as well as supported by adequate facilities and infrastructure. Purpose : To determine the Perceptions of midwifery services with the satisfaction of pregnant women in antenatal care in Health Centre 2021. Method : An analytic with a cross-sectional approach. The population were 83 pregnant women who did antenatal care examinations in August–October. Data analysis used chi-square test. Results : There was a relationship between perceived reliability and satisfaction of pregnant women (p = .015<.05). There was a relationship between perception of responsiveness and satisfaction of pregnant women (p = .020<.05). There was a relationship between the perception of security and satisfaction of pregnant women (p = .037<.05). There is a relationship between perception of empathy and satisfaction of pregnant women (p = .028<.05). There was a direct correlation between the perception of evidence and the satisfaction of pregnant women (p = .037<.05). Conclusion : There was a relationship between perceptions of reliability, responsiveness, assurance, empathy and direct evidence with the satisfaction of pregnant women in Antenatal Care in Health Centre 2021. It is recommended for health workers to improve health promotion regarding the importance of health promotion visiting Antenatal Care (ANC) for pregnant women.